Inference as a Pragma linguistic Phenomenon - Mаftunа Gаziеvа (Zien Journals, 2023)
The article discusses the phenomenon of inference related to pragmalinguistics. The phenomenon of inference is distinguished by its involvement in the implicative structure of the sentence. Also, the phenomenon of inference is a concept related to the addressee.
Keywords: pragmalinguistics; inference; implicative structure